Enhanced visible light catalysis activity of CdS-sheathed SrAl2O4:Eu2+, Dy3+ nanocomposites. Issue 24 (29th May 2018) - Xiao, Yanhe; Luo, Bin; Cheng, Baochang; Huang, Qianfei; Ye, Yalong; Fang, Liting; Zhou, Lin; Lei, Shuijin
Abstract : For CdS-sheathed SrAl2 O4 :Eu 2+, Dy 3+ composites, there exists a tremendous contact interface, and moreover, holes can effectively transfer from the phosphor to the CdS semiconductor. Therefore, they can show a significant enhanced effect for visible light photocatalysis. Abstract : SrAl2 O4 :Eu 2+, Dy 3+ long afterglow phosphors with one-dimensional nanostructures were synthesized by a hydrothermal method followed by post-annealing, and subsequently CdS was uniformly coated on their surfaces by a sol–gel approach. The nanocomposite system can significantly enhance the photocatalytic activity for the degradation of methyl orange and hexavalent chromium under ultraviolet and visible light irradiation. After the modification treatment with a 1 : 2 molar ratio of CdS to SrAl2 O4 :Eu 2+, Dy 3+ nanophosphors, the degradation rate of methyl orange can increase by 2.5 times and reach a maximum of 96.3% under visible light illumination for 30 min. The enhancement of photocatalytic activity originates from the improvement of light usage efficiency due to the hole migration from SrAl2 O4 :Eu 2+, Dy 3+ phosphors to the CdS semiconductor and the reutilization of SrAl2 O4 :Eu 2+, Dy 3+ luminescence.